Exploring Factors Affecting Intention to Use Chatgpt for Searching Finance-Related Information - Kelvin Lee, Yong Ming; Mohamad, Jais; Yang, Ling Hui; Ling, Pick Soon; Agnes Lim, Siang Siew; Liew, Siew Ling (Human Resource Management Academic Research Society (HRMARS), 2023)
The emergence of ChatGPT has revolutionized information seeking behavior. This study aims to explore the potential factors that influence the adoption of ChatGPT as a tool for searching finance related information. This study also distributed the online questionnaire to gather the responses from existing users. The findings indicate that ease of use, usefulness, herding behavior, and social influence significantly affect users’ intention to use ChatGPT for searching finance related information. However, this study also revealed that there is no significant relationship between individuals who used ChatGPT for searching finance related information and their intention for information checking. These results provide valuable insights for future studies and underscore the potential of ChatGPT as a tool for searching finance related information.